The Effect of Physical Activity on Mental Health: Literature Review and Implications for Daily Life - Putra, Saddan Pramana; Mandalawati, Titin Kuntum; Utomo, Ardyansyah Arief Budi; Darmawan, Agung Dwi; Prasetyo, Yona Bayu (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. Sport and physical activity have a great impact on an individual's mental well-being. This suggests that in challenging situations, individuals can find ways to stay physically active, which in turn can help reduce stress and anxiety. Through this literature review, this study aims to explore the effects of physical activity on mental health and understand how it contributes to everyday life. Materials and methods. This study utilised the Guidelines for Systematic Reporting and Meta-Analysis (PRISMA) method to ensure completeness and accuracy. The period covered in this study was from 2019 to 2024, total articles n=15. Results. There is a strong link between physical activity and mental well-being. Physical activity can serve as an effective intervention to address mental health issues, such as depression and anxiety. In addition, regular physical activity can also help boost self-confidence and improve body perception, which in turn supports more optimal mental health. Conclusion. Regular engagement in exercise can lead to significant improvements in mood, reductions in anxiety and depression, and improvements in overall psychological well-being. Increased awareness and support for physical activity is expected to lead to a healthier society, both mentally and physically.